Reliability of parent report measures of behaviour in children with Down syndrome - Esbensen, Anna J. (J Intellect Disabil Res, 2018)
BACKGROUND: Behavioural problems are common among children with Down syndrome (DS). Tools to detect and evaluate maladaptive behaviours have been developed for typically developing (TD) children and have been evaluated for use among children with intellectual and developmental disabilities (IDD). However, these measures have not been evaluated for use specifically in children with DS. This psychometric evaluation is important given that some clinically observed behaviours are not addressed in currently available rating scales. The current study evaluates the psychometric properties of the Child Behavior Checklist (CBCL), a commonly used screening tool developed for TD children and commonly used with children with IDD. METHOD: The study investigated psychometric properties of the CBCL among school-age children with DS, including an assessment of the rate of detecting behaviour problems, concerns with distribution, internal consistency, inter-rater reliability, and convergent and discriminant validity with the Aberrant Behavior Checklist (ABC) and Nisonger Child Behavior Rating Form (NCBRF). Caregivers of 88 children with DS aged 6–18 years rated their child’s behaviour with the CBCL, ABC, and NCBRF. Teachers completed the Teacher Report Form (TRF). RESULTS: About 1/3 of children with DS were reported to exhibit behaviours of clinical concern on the total score of the CBCL. Internal consistency for CBCL subscales was poor to excellent, and inter-rater reliability was generally acceptable. The subscales of the CBCL performed best when evaluating convergent validity, with variable discriminant validity. Normative data conversions controlled for age and gender differences in this sample. CONCLUSION: The study findings suggest that, among children with DS, some CBCL subscales generally performed in a psychometrically sound and theoretically appropriate manner in relation to other measures of behaviour. Caution is warranted when interpreting specific subscales (Anxious/Depressed, Somatic Complaints, and Thought Problems). The CBCL can continue to be used as a screening measure when evaluating behavioural concerns among children with DS, acknowledging poor discriminant validity and that key behaviour concerns in DS may not be captured by the CBCL screen.